Geometry, Allometry and Biomechanics of Fern Leaf Petioles: Their Significance for the Evolution of Functional and Ecological Diversity Within the Pteridaceae - Mahley, Jennifer N.; Pittermann, Jarmila; Rowe, Nick; Baer, Alex; Watkins, James E.; Schuettpelz, Eric; Wheeler, James K.; Mehltreter, Klaus; Windham, Michael; Testo, Weston; Beck, James (Frontiers in Plant Science, 2018)
Herbaceous plants rely on a combination of turgor, ground tissues and geometry for mechanical support of leaves and stems. Unlike most angiosperms however, ferns employ a sub-dermal layer of fibers, known as a hypodermal sterome, for support of their leaves. The sterome is nearly ubiquitous in ferns, but nothing is known about its role in leaf biomechanics. The goal of this research was to characterize sterome attributes in ferns that experience a broad range of mechanical stresses, as imposed by their aquatic, xeric, epiphytic, and terrestrial niches. Members of the Pteridaceae meet this criteria well. The anatomical and functional morphometrics along with published values of tissue moduli were used to model petiole flexural rigidity and susceptibility to buckling in 20 species of the Pteridaceae. Strong allometric relationships were observed between sterome thickness and leaf size, with the sterome contributing over 97% to petiole flexural rigidity. Surprisingly, the small-statured cheilanthoid ferns allocated the highest fraction of their petiole to the sterome, while large leaves exploited aspects of geometry (second moment of area) to achieve bending resistance. This pattern also revealed an economy of function in which increasing sterome thickness was associated with decreasing fiber cell reinforcement, and fiber wall fraction. Lastly, strong petioles were associated with durable leaves, as approximated by specific leaf area. This study reveals meaningful patterns in fern leaf biomechanics that align with species leaf size, sterome attributes and life-history strategy.